2019
DOI: 10.1186/s12866-019-1664-7
|View full text |Cite
|
Sign up to set email alerts
|

Pan-genome diversification and recombination in Cronobacter sakazakii, an opportunistic pathogen in neonates, and insights to its xerotolerant lifestyle

Abstract: BackgroundCronobacter sakazakii is an emerging opportunistic bacterial pathogen known to cause neonatal and pediatric infections, including meningitis, necrotizing enterocolitis, and bacteremia. Multiple disease outbreaks of C. sakazakii have been documented in the past few decades, yet little is known of its genomic diversity, adaptation, and evolution. Here, we analyzed the pan-genome characteristics and phylogenetic relationships of 237 genomes of C. sakazakii and 48 genomes of related Cronobacter species i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
(127 reference statements)
3
7
0
Order By: Relevance
“…The resulting correlation pro le exhibited a monotonic decay ( Figure 5B), indicating the presence of recombination. Similar decaying correlation pro les have also been shown in other recombining bacteria, such as Helicobacter pylori, Pseudomonas aeruginosa, Salmonella enterica and Cronobacter sakazakii [63][64][65]. Meanwhile, the mcorr showed the mean fragment size (f̅ ) of a recombination event in M. luteus species was 874.45 bp; the recombination coverage (c), which indicates the proportion of sites in the genome whose diversity has come from recombination events since its last common ancestor, was 0.46; and the ratio γ/μ, the relative rate of recombination to mutation, was 10.87 ( Figure 5C).…”
Section: High Level Of Homologous Recombination In M Luteus Speciessupporting
confidence: 72%
“…The resulting correlation pro le exhibited a monotonic decay ( Figure 5B), indicating the presence of recombination. Similar decaying correlation pro les have also been shown in other recombining bacteria, such as Helicobacter pylori, Pseudomonas aeruginosa, Salmonella enterica and Cronobacter sakazakii [63][64][65]. Meanwhile, the mcorr showed the mean fragment size (f̅ ) of a recombination event in M. luteus species was 874.45 bp; the recombination coverage (c), which indicates the proportion of sites in the genome whose diversity has come from recombination events since its last common ancestor, was 0.46; and the ratio γ/μ, the relative rate of recombination to mutation, was 10.87 ( Figure 5C).…”
Section: High Level Of Homologous Recombination In M Luteus Speciessupporting
confidence: 72%
“…Population structure analysis including 15 genomes in this study and an additional 108 reference genomes further revealed that the STs of C. sakazakii formed their own distinct cluster, which was in agreement with previous studies ( Lee and Andam, 2019 ; Jang et al, 2020 ). Therefore, it is essential to recognize more STs to aid in epidemiological investigations and risk assessments of this pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…4 b), indicating the presence of recombination. Similar decaying correlation profiles have also been shown in other recombining bacteria, such as Helicobacter pylori , Pseudomonas aeruginosa , Salmonella enterica and Cronobacter sakazakii [ 41 43 ]. Meanwhile, mcorr showed the mean fragment size (f̅) of a recombination event in M. luteus species was 874.45 bp; the recombination coverage (c), which indicates the proportion of sites in the genome whose diversity has come from recombination events since its last common ancestor, was 0.46; and the ratio γ/μ, the relative rate of recombination to mutation, was 10.87 (Fig.…”
Section: Resultssupporting
confidence: 70%